Influence of auditor quality and audit committee effectiveness on earnings conservatism of Malaysian public listed firms - Ahamad Rapani, Nor Hanani (Curtin University, 2011)
This study investigates whether earnings conservatism is significantly higher amongst Malaysian publicly listed firms subject to higher standards of ‗direct custodian excellence‘ of the financial reporting system relative to counterparts subject to lower direct custodian excellence standards. Drawing on agency theory, supplemented by tenets of key corporate governance reforms undertaken in Malaysia since the Asian financial crisis in 1997, it is expected that direct custodian excellence is positively associated with earnings conservatism.For purposes of the main analysis, conservatism is defined in terms of both timeliness and persistence, and measured using models developed by Basu (1997). Direct custodian excellence, meanwhile, is derived as the function of audit quality (measured as a function of independence, specialization and brand name) and audit committee effectiveness (measured as a function of independence, financial expertise and diligence). Analysis is based on annual data (spanning the years 2002 to 2007) collected from 100 randomly selected Malaysian firms listed continuously on the Bursa Malaysia from January 1 2002 till December 31 2007) for each annual period from 2002 to 2007. Following exclusions for missing data points and outliers, empirical analysis is based on a final useable sample of 577 firm-year observations.Findings from an extensive analytical analysis show limited support for the study‘s general proposition. Rather, findings show the level of earnings conservatism is likely to be equivalent for a Malaysian publicly listed firm subject to higher standards of direct custodian excellence than a counterpart facing lower levels of direct custodian excellence. There is some evidence, however, supporting the view that a Malaysian publicly listed firm engaging a higher quality auditor is more likely to have higher levels of persistent earnings conservatism than a counterpart using the services of a lower quality external auditor. Additional analysis, meanwhile, suggests a lack of association between audit committee effectiveness and (both the timeliness and persistence of) earnings conservatism within the Malaysian capital market setting. Overall, findings provide valuable insights and understanding, not only in respect to the direct custodian excellence/earnings conservatism linkage, but the individual dynamics and significance of corporate governance and earnings conservatism concepts."